CROSS-SECTIONAL SURVEY TO ASSESS THE BENEFICIARIES EXPERIENCE REGARDING COVID-19 VACCINATION IN VACCINATED CANDIDATES IN A TRIBAL DISTRICT OF RAJASTHAN - EMIGH PROSPECTIVE - Bhujade, Rashmi; Yadav, Kanak; Kumar, Jignesh; Pukar, Mahesh; Bhatt, Ravi; Baghel, Anil Singh; Ray, ShashiKANT; Kumar, Rakesh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: A year with COVID-19 has been a harrowing breakneck journey. On 11th March 2020, the World Health Organization declared COVID-19 as a pandemic. It spread across globe in span of 3 months; this is how emergence of unknown virus became a multifaceted pandemic. Till date, no definitive treatment of covid-19 is available, except hope of vaccination. We must ensure safe and effective vaccination to protect people. It has been largest vaccination drive, that’s why important to know the beneficiary’s point of view regarding covid vaccination process, so that the result of this study can be used to amend the process if needed, to make the process more beneficiary friendly. Methods: A cross-sectional study was conducted in a government covid vaccination centerto assess the beneficiaries prospective about their experience of covid-19 vaccine. The study duration was 6 months. Data were collected with the help of semi-structured pro forma. Results: Data analysis was done with the help of SPSS-20. Approximately 93% of participants received vaccination appointment. Around 58% of participants were screened for COVID-19 symptoms. Most (90%) participants said that physical distancing was maintained during vaccination, 93% participants were informed about of vaccination process, 85% participants mentioned that staff had explained about adverse event following immunization (AEFI) before vaccination, and 76% of participants mentioned that they received Covishied, only 1 participant reported AEFI within 30 min of waiting period, and he received the preliminary treatment at vaccination center. Conclusion: Feedback from the user is a good way to quality check; their reviews give the opportunity to improve. Most of the vaccines were satisfied with the vaccination procedure.